Deficiências e incapacidades por hanseníase na atenção secundária à saúde - Santana , Emmanuelle Malzac Freire de (2017)
Introduction: Leprosy is a disease that causes impairments in physical, emotional and social spheres. Aim: To analyze the disabilities and impairments caused by leprosy according to the body site affected and the type of disability. Method: This is a quantitative, descriptive, retrospective, population-based and documentary study developed from 2009 to 2014 in a reference center for leprosy in João Pessoa-PB. It involved 414 medical records and were collected diagnosis and discharge data about sociodemographic, clinical and simplified neurological evaluation variables. Data were analyzed using descriptive and inferential statistics techniques. The project was approved by the Research Ethics Committee of Federal University of Paraíba under protocol 443/14, CAAE 34284414.3.0000.5188. Results: There was a predominance of men (58.7%), age between 31 and 45 years (27.8%), low level of schooling (65.9%), multibacillary cases (60.6%), dimorphous form (35%), disability degree of zero (59.4%), feet compromised (37.2%) and no affected nerves (52.4%). There was a significant difference between 2009 and 2014 for the disability degree (p = 0.038), eye body site (p = 0.004), hand body site (p = 0.003) and for the nerves affected (p = 0.020). When comparing diagnosis and discharge, there was a decrease in the involvement of the nose body site (p < 0.001), the disabilities (dryness p = 0.002 and wound p = 0,000 in the nose and ulcer p = 0.004 in the feet) and the amount of affected nerves (p = 0.000). Male sex, low level of schooling, multibacillary classification, neural form and presence of affected nerves were identified as factors associated with the development of disabilities, being a greater possibility of post-discharge sequelae. Conclusion: This study highlights a reduction in the magnitude of the endemic disease and the possible effectiveness of the assistance in the prevention and rehabilitation of disabilities. The need for patient follow-up in post-discharge and surveillance of the identified groups is also highlightened.